1997
DOI: 10.1093/ndt/12.8.1652
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vivo effects of amino-acid-based and bicarbonate-buffered peritoneal dialysis solutions with regard to peritoneal transport and cytokines/prostanoids dialysate concentrations

Abstract: Application of an amino-acid/bicarbonate solution resulted in a small but significant increase in peritoneal permeability. Also increased concentrations of various cytokines/prostanoids were measured in the effluent. According to in vitro testing with mononuclear phagocytes both bicarbonate-buffered fluids were to the same extent less inhibitory to certain cell functions than lactate-buffered solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 2 publications
3
19
0
Order By: Relevance
“…Others have reported that a 2.6% amino acid peritoneal dialysis solution induced an increased loss of macromolecules including albumin and IgG and the small molecular weight amino acids, which was accompanied by an increased prostanoid generation in the peritoneal cavity [ 12 ]. One percent AA solutions were also found to stimulate protein losses and release of prostanoids and several proinflammatory cytokines consistent with an increase in peritoneal blood flow and effective peritoneal surface area [ 13 , 14 ]. In some studies, however, no significant effect on protein losses or release of prostanoids was found [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Others have reported that a 2.6% amino acid peritoneal dialysis solution induced an increased loss of macromolecules including albumin and IgG and the small molecular weight amino acids, which was accompanied by an increased prostanoid generation in the peritoneal cavity [ 12 ]. One percent AA solutions were also found to stimulate protein losses and release of prostanoids and several proinflammatory cytokines consistent with an increase in peritoneal blood flow and effective peritoneal surface area [ 13 , 14 ]. In some studies, however, no significant effect on protein losses or release of prostanoids was found [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plum et al [31] and Martikainen et al [32] who detected increased intraperitoneal levels of IL-6 in patients receiving amino-acid-based solutions and linked this effect to better preservation of HPMC. Moreover, it has been demonstrated that the dialysate from patients treated with amino-acid-based solutions contained increased concentrations of PGE 2 [31,33]. One may hypothesize that those increased PGE 2 levels were of mesothelial origin.…”
Section: Discussionmentioning
confidence: 99%
“…Plum et al reported that application of amino acid/bicarbonate-containing PDF resulted in significantly higher dialysate TNF concentrations when compared with glucose/bicarbonate-containing solutions. 9 A limited number of in vivo studies analyzed the effects of different glucose concentrations on IL-6 and TNF-a release from peritoneal or peripheral blood macrophages, monocytes or mesothelial cells. Douvdevani et al studied the in vitro effect of dialysis fluid on the basal and lipopolysaccharide stimulated release of IL-1b and TNF-a by peritoneal macrophages and peripheral blood mononuclear cells (PBMC), and the time course and factors involved in this effect.…”
Section: Discussionmentioning
confidence: 99%